Water‐induced mechanically adaptive behavior of carboxylated acrylonitrile‐butadiene rubber reinforced by bacterial cellulose whiskers. Issue 1 (17th April 2018) - Chen, Yang; Wang, Liping; Yin, Qing; Jia, Hongbing; Wang, Dongni; Li, Geng; Yin, Biao; Ji, Qingmin; Xu, Zhaodong
Abstract : Water‐induced mechanically adaptive rubber nanocomposites were prepared by mixing bacterial cellulose whiskers (BCWs) suspension with carboxylated acerlonitrile‐butadiene rubber (XNBR) latex, followed by latex blending method. The introduction of BCWs into XNBR enhanced the tensile storage modulus ( E ') significantly, which originated from the formation of a rigid 3D filler network within matrix as well as the interfacial interaction between filler and matrix. The water uptake ratio of nanocomposite films increased with BCWs content, from 5.5% for neat XNBR to 54% for nanocomposite with 20 phr (parts per hundred rubber) BCWs. Upon submersed in water, the nanocomposite films showed dramatic decrease in E′, especially for which filled with high BCWs loadings. For example, E′ of nanocomposite with 20 phr BCWs was decreased by 98.04% after equilibrium swelling compared with only 52.02% for nanocomposite with 3 phr BCWs. The remarkable water‐triggered modulus changes are attributed to the disentanglement of BCWs network after swelling. The prepared XNBR–BCWs nanocomposites with mechanically adaptive properties could contribute to develop the new type of rubber‐based smart materials. POLYM. ENG. SCI., 59:58–65, 2019. © 2018 Society of Plastics Engineers